Improving Sustainable Development Outcomes Through Best Management Practices - Ramirez, Byron (Consilience, 2014)
Over the last several decades the world has undergone several economic, political, environmental, and cultural changes. Society is faced with countless challenges that surround sustainable development. Progress has been made with respect to world poverty, technological development, and environmental awareness. Nonetheless, we have an opportunity to improve the leadership, planning, implementation, and monitoring of sustainable development projects. Notwithstanding having better technology and increased access to more data and information, we are still not able to optimize sustainable development decisions. This paper addresses a few critical aspects of strategic management and some resulting challenges faced by policy makers, managers, and implementers of sustainable development projects who come from the private sector, public sector and NGOs. The paper offers some managerial recommendations on how to enhance the leadership, planning, implementation, and monitoring of sustainable development projects.